Pityriasis rosea after administration of Pfizer-BioNTech COVID-19 vaccine - Olivia G. Cohen; Ashley K. Clark; Heather Milbar; Mordechai Tarlow (Taylor & Francis Group, 2021)
Pityriasis rosea (PR) is an acute papulosquamous cutaneous disorder that classically presents with a herald patch rapidly followed by a widespread rash along skin cleavage lines. Although the exact pathogenesis of PR is unknown, current evidence suggests that an inflammatory reaction due to a viral trigger may lead to the cutaneous manifestations. COVID-19 has been reported as one such viral trigger for PR. Previously, PR has been reported in temporal association with various viral inoculations. This article presents a case of PR in a 66-year-old black male 1 week after administration of the Pfizer-BioNTech COVID-19 vaccine.